If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(3x+1)=2(8-x)
We move all terms to the left:
3(3x+1)-(2(8-x))=0
We add all the numbers together, and all the variables
3(3x+1)-(2(-1x+8))=0
We multiply parentheses
9x-(2(-1x+8))+3=0
We calculate terms in parentheses: -(2(-1x+8)), so:We get rid of parentheses
2(-1x+8)
We multiply parentheses
-2x+16
Back to the equation:
-(-2x+16)
9x+2x-16+3=0
We add all the numbers together, and all the variables
11x-13=0
We move all terms containing x to the left, all other terms to the right
11x=13
x=13/11
x=1+2/11
| 23-x=44 | | 0=2x^2+3x+15 | | 5–3(7n+8)= | | 32=d-17 | | 5m-10=2m+20 | | 7+3=2y | | 3^x-3^x+2=-72 | | 5x-10=6x+35x-106x+3 | | -x⁵+5x+1=0 | | -{x}^{5}+5x+1=0 | | X=68y | | Y=68x | | 125m-75m=43,875-175m | | Y=0x-32 | | Y=-0,25x-32 | | 7x+65=-19 | | (7/14)^x=11/7 | | y+0.3y-2.2=-5.8(y*6.5) | | Y=-32+5x | | 6.7g+8=4.7g+20 | | 5.2=4x-7.6 | | 2y×4y+3=16 | | x2-8x+56=0 | | 5x(2-x)=3x | | 180-3x²=0 | | 12−m=7 | | 29+(8-17x)=7-4(5-2x | | F(x)=6•2^x | | b+3–20=–4 | | X=3,7+87000y | | 5y+2y+8+3= | | 6z/7=2 |